2019
DOI: 10.1007/s10840-019-00537-8
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial voltage mapping: defining and targeting the atrial fibrillation substrate

Abstract: Low atrial endocardial bipolar voltage, measured during catheter ablation for atrial fibrillation (AF), is a commonly used surrogate marker for the presence of atrial fibrosis. Low voltage shows many useful associations with clinical outcomes, comorbidities and has links to trigger sites for AF. Several contemporary trials have shown promise in targeting low voltage areas as the substrate for AF ablation; however, the results have been mixed. In order to understand these results, a thorough understanding of vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 89 publications
(94 reference statements)
0
63
0
3
Order By: Relevance
“…In this context, low atrial bipolar voltage as a marker of left atrial fibrosis is proposed as a potential contributor that may affect the biophysics of energy delivery during RFA. Specific voltage thresholds to define atrial scarring have not been histologically validated (Sim et al, 2019). In a study of 20 patients with paroxysmal AF, Kapa et al (2014) evaluated thresholds for atrial scarring and reported different cut offs for different segments of the left atrium.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, low atrial bipolar voltage as a marker of left atrial fibrosis is proposed as a potential contributor that may affect the biophysics of energy delivery during RFA. Specific voltage thresholds to define atrial scarring have not been histologically validated (Sim et al, 2019). In a study of 20 patients with paroxysmal AF, Kapa et al (2014) evaluated thresholds for atrial scarring and reported different cut offs for different segments of the left atrium.…”
Section: Discussionmentioning
confidence: 99%
“…Wider or narrower electrode spacing distances influences travel time (or along the same lines, lesser or greater velocity of the depolarization respectively) and will result in differences in amplitude and thus morphology of recording. 27 There is also evidence to show that increasing interelectrode distance leads to increased voltages but only in select patients. 28 Furthermore, larger sized electrodes which cover greater area may potentially demonstrate increased voltage readings, such as those elicited by Marcus et al 29 although this is not the case universally.…”
Section: Identifi C Ati On Of the Sc Ar Burden In Af And In S Rmentioning
confidence: 99%
“…Поэтому, вместо гистологического определения, в большинстве современных исследований определена амплитуда сигнала рубца <0,05 мВ как значение, которое первоначально возникло из базового шума ранних электроанатомических систем картирования [15]. Кроме того, значение 0,5 мВ, которое широко используется для определения низкого вольтажа, хотя и удобно, но не обосновано наличием подтверждённых патологических изменений в структуре или функции предсердий [19].…”
Section: развитие метода биполярного элетроанатомического картированияunclassified